Deriving Antibiotic Thresholds Under a One Health Framework: Integrating Bioaccumulation and Human Exposure in the Yangtze River Estuary Food Web - Ya-Qian Xu; Qian Li; Xinyang Zhang; Xingpan Guo; Ye Huang; Xinran Liu; Nan Lin (Environmental Science & Technology, 2026)
Abstract Antibiotics are widely detected in aquatic environments, yet current environmental thresholds rarely integrate ecological and human health risks under a One Health framework. Here, we developed a bioaccumulation- and human exposure-based approach to derive health-protective environmental thresholds for antibiotics in the Yangtze River Estuary (YRE). Total antibiotic concentrations averaged 6.64 ± 5.91 ng/L in water, 9.65 ± 7.55 ng/g in sediment, and 56.4 ± 80.9 ng/g in aquatic organisms, with significant cross-compartmental variability and distinct compositional patterns among environmental matrices. Chloramphenicol (CAP) exhibited the strongest bioaccumulation potential (BCF up to 20,190 L/g) and was the only compound showing trophic magnification (TMF = 2.97), whereas most other antibiotics displayed trophic dilution. Derived thresholds ranged from 2.04 × 10–5–434 ng/L for water and 3.01 × 10–4–17.0 ng/g for sediment, several orders of magnitude lower than thresholds derived using traditional ecotoxicity-based approaches in previous studies. CAP, norfloxacin, and ofloxacin were identified as priority risk compounds, demonstrating that even moderate environmental concentrations can bioaccumulate through aquatic food webs and pose notable dietary exposure risks to consumers. This framework provides a more protective basis for antibiotic pollution management and environmental standard development under a One Health perspective.